Adaptation of fodder mixtures at different levels of amendment and irrigation in Nariño, Colombia - Portillo López, Paola Andrea; Meneses Buitrago, Diego Hernán; Lagos Burbano, Elizabeth; Duter Nisivoccia, María E.; Castro Rincón, Edwin (Agronomía Mesoamericana, 2021)
Introduction. Specialized dairy farming in the high tropics of Nariño faces with different limitations, such as the variability and seasonality of the fodder supply. Objective. To evaluate six mixtures of perennial, annual, and leguminous fodder, three levels of amendment and two levels of irrigation in the high tropic of Nariño. Materials and methods. The study was developed between December 2017 and November 2018 at the Obonuco research center of the Colombian Agricultural Research Corporation. A complete randomized block design was used, with an arrangement of subdivided plots. It was measured: vigor, height, coverage, number of leaves, incidence of pests, incidence and severity of diseases, nutritional deficiencies, and dry matter (MS). Software R V.3.6.0 was used for the analysis. Results. The association (gramineous and leguminous) generated a direct effect on the yield of MS, cover, and number of leaves, being the best mixture the one composed by Dactylis glomerata, Trifolium repens L., and Trifolium pratense L. For the variable height, the highest values were presented in the Tetrablend 260 mixture. Most of the treatments were kept on scales without damage and slight damage for the variables incidence of pests, severity of diseases and nutritional deficiencies. Conclusion. The mixtures of grasses and legumes showed comparative advantages over pure grass monoculture in terms of MS yield and agronomic variables. In general, all the treatments were kept in minimum and light damage thresholds for the phytosanitary variables.